Biomechanics of adjacent segment after three-level lumbar fusion, hybrid single-level semi-rigid fixation with two-level lumbar fusion. Issue 4 (16th March 2022) - Zhang, Mingzheng; Ren, Weiyan; Mo, Zhongjun; Li, Jian; Pu, Fang; Fan, Yubo
Abstract: Multi-level spinal fusion has been reported in some cases to lead to adjacent segment disease (ASD) and proximal junctional kyphosis (PJK). The purpose of this study was to demonstrate a polyether-ether-ketone (PEEK) rod fixation system implanted adjacent to a two-level lumbar fusion would have a lower risk of PJK than three-level lumbar fusion, which was investigated by comparing the biomechanical effects on the adjacent level after surgical procedures. Four finite element (FE) models of the lumbar-sacral spine (intact model (INT), L4-S1 fusion model (L4-S1 FUS), L3-S1 fusion model (L3-S1 FUS), and single-level PEEK rod semi-rigid fixation adjacent to L4-S1 fusion model (FUSPRF)) were established. Displacement-controlled finite element (FE) analysis was used during the simulation. Compared with the two-level fusion model (L4-S1 FUS), both three-level implanted models (L3-S1 FUS and FUSPRF) showed an increase intersegmental rotation angle, and maximum von-Mises stress on the disc annulus. The results also showed that the intersegmental rotation, stress on the disc annulus and maximum stress on the rod were lower in the FUSPRF model than the L3-S1 FUS model. Though the maximum screw stress was higher in the FUSPRF model than the L3-S1 FUS model under all moments except for torsion, the maximum screw stress in the two models were far below the yield strength of titanium alloy. As the parameters above have been indicated as risk factors for PJK, it can be concluded that hybrid single-level PEEK rod semi-rigid fixation and two-level lumbar fusion have a lower risk of PJK than three-level lumbar fusion.